1986
DOI: 10.1016/s0022-5347(17)45236-0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Ureterovesical Junction: Interaction Between Diuresis and Detrusor Instability at the Ureterovesical Junction in Pigs

Abstract: In pigs under general anesthesia, the mutual relation between ureterovesical flow and detrusor activity was evaluated with juxtavesical ureteral perfusion pressure measurements and cystometry. At constant bladder filling volume ureterovesical perfusion could provoke detrusor activity, which was positively related to the perfusion rate, and which disappeared after perfusion was stopped. During such involuntary detrusor activity ureterovesical perfusion pressure might increase significantly more than intravesica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Our report with more study population revealed that desmopressin was statistically effective in reducing nocturnal voids in both groups in a longer treatment period (22.28 ± 13.32 months in non‐NP, 23.95 ± 14.80 months in NP). Animal study had observed desmopressin induced increase in nighttime voided volume as a result of a slower rate of bladder filling and regulated bladder activity to decrease nocturia by affecting bladder‐related neurons in the micturition center . Further, if the nocturnal urine output can be reduced, nocturnal frequency because of detrusor overactivity or small bladder capacity can also be reduced in these elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our report with more study population revealed that desmopressin was statistically effective in reducing nocturnal voids in both groups in a longer treatment period (22.28 ± 13.32 months in non‐NP, 23.95 ± 14.80 months in NP). Animal study had observed desmopressin induced increase in nighttime voided volume as a result of a slower rate of bladder filling and regulated bladder activity to decrease nocturia by affecting bladder‐related neurons in the micturition center . Further, if the nocturnal urine output can be reduced, nocturnal frequency because of detrusor overactivity or small bladder capacity can also be reduced in these elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Desmopressin suppresses bladder activity by inhibiting type E1 neurons or activating type I neurons. Moreover, ureterovesical flow has been demonstrated to trigger local and general detrusor activity in an unstable bladder by distension of detrusor muscle bundles around the ureteric hiatus detrusor activity in a pig model (24). Based on these findings, desmopressin treatment would improve the decreased NBC seen in mixed nocturia patients by suppressing detrusor activity and inhibiting neuron-associated bladder contraction and the ureterovesical flow rate during sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Average nighttime voided volumes still remained lower than both the bladder capacities (MVVs) and the maximal observed nocturnal bladder volumes. Observed desmopressin-induced 20% increase in average nighttime voided volume in patients with increased NBCi before treatment may have been due to a slower rate of bladder filling, as was found in a study involving pigs [21]. In addition, desmopressin modulates the activity of the brainstem micturition center, as discussed by Lee et al [20] in studies on rats [22].…”
Section: Discussionmentioning
confidence: 81%